Short communication. Computer vision applied to saffron flower (Crocus sativus L.) processing - Perez-Vidal, C.; Gracia, L.; Gracia, C. (Spanish Journal of Agricultural Research, 2011)
<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">This paper presents a computer vision system to obtain, using image analysis, the optimal cutting point of saffron flowers in order to obtain their stigmas. For this purpose, an effective and flexible computer program has been developed to process the flower image in order to obtain the cutting point to be sent to the cutting element. Furthermore, experimentation with real saffron flowers has been carried out in order to validate the developed application. In particular, the tests show that the method has good robustness and high success percentage in the flower characterization regardless the shape and size of the flower. The high image processing rate of the proposed method (20 computations s<span style="font-size: 6pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">–1<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">) would allow to greatly increase the production rate obtained with an automated cutting system compared to that obtained with the traditional hand method.